Examining Consistency Among Observers in MRI Assessment of Lumbar Disc Disease and its Clinical Consequences: An In-Depth Investigation in a Developing Nation - Siddiqui, Uzair; Hussain, Manzar; Nasir, Sadaf; Shamim, Bushra (International Journal of Innovative Research in Medical Science, 2024)
This study aims to investigate the inter-observer consistency among two qualified neuro-radiologists and a neurosurgeon in the assessment of nerve root compression on MRI. The primary objective is to explore the consistency and discordance in their interpretations, shedding light on the reliability of radiological evaluations in identifying nerve root compression. This correlation analysis has direct implications for clinical decision-making, potentially altering the management algorithm by influencing the decision to pursue surgery or opt for a non-surgical approach. Notably, this study represents the largest series reporting such analyses from a third-world country, contributing valuable insights into the context-specific challenges and nuances associated with neuroimaging assessments in resource-constrained settings.